2013
DOI: 10.1002/micr.22166
|View full text |Cite
|
Sign up to set email alerts
|

Partial failure of a perforator free flap can be salvaged by a second perforator free flap

Abstract: The root cause of partial failure of a perforator free flap was found to be either iatrogenic or de novo in origin. The proper design requires an awareness of the correct topographic axis and an understanding of the perforasome concept to better insure adequate flap perfusion. If a free flap is still considered the best solution after a partial failure, the advantages and benefit of a second perforator free flap should not be overlooked.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 28 publications
(46 reference statements)
0
16
0
Order By: Relevance
“…They appeal to reconstructive surgeons because of preservation of the main arteries, minimal donor site injury and great flexibility in design [7,8,10]. A proper flap design requires an awareness of the correct topographic axis and an understanding of the perforator to insure adequate flap perfusion [9]. Surgeons also need to obtain comprehensive insight into the systematic and detailed anatomy to guide the surgical procedure.…”
Section: Introductionmentioning
confidence: 99%
“…They appeal to reconstructive surgeons because of preservation of the main arteries, minimal donor site injury and great flexibility in design [7,8,10]. A proper flap design requires an awareness of the correct topographic axis and an understanding of the perforator to insure adequate flap perfusion [9]. Surgeons also need to obtain comprehensive insight into the systematic and detailed anatomy to guide the surgical procedure.…”
Section: Introductionmentioning
confidence: 99%
“…Hallock GG (Hallock, 2014) reported that according to their experience all perforator free flaps that had some form of partial failure were Although this is not a large series, there were no partial or total flap necrosis reported in seventeen extended ALT flaps.…”
Section: Discussionmentioning
confidence: 81%
“…Hallock GG (Hallock, ) reported that according to their experience all perforator free flaps that had some form of partial failure were ALT free flaps. Initially this was clinically unrecognizable, but ultimately distal flap ischemia was attributed to poor flap design.…”
Section: Discussionmentioning
confidence: 99%
“…As experience with perforator free flaps continues to increase, so does the evidence base pertaining to the management of partial flap failures in context of patent microanastomoses (Acland, Anderson, Siemionow, & McCabe, ; Blondeel, & Neligan, 2013; Hallock, ; Pignatti, Iwuagwu, & Browne, ; Weinzweig & Gonzalez, ). Hallock () described using the viable portion of a partially failed free radial forearm flap as a “bridge” flap to revascularize a second free gracilis muscle flap, to cover exposed bone from a previous mid‐foot amputation.…”
Section: Discussionmentioning
confidence: 99%
“…The descending branch of the lateral circumflex femoral artery of the secondary ALT flap was anastomosed end‐to‐side to the arterial perforator of the original flap, and a single vena comitans of the secondary flap was coupled end‐to‐end to the distal end of the vena comitans of the primary flap. Utilizing the patent pedicle in this way obviated the search for additional recipient vessels, reducing the surgical morbidity to the patient significantly (Hallock, ). In the current case, we have employed a similar salvage procedure to anastomose stacked free flaps onto the original patent pedicle and facilitate optimal soft tissue reconstruction with minimal further surgical morbidity.…”
Section: Discussionmentioning
confidence: 99%